The Role of Maranao Traditional Leaders and Local Political Leaders towards Collaboration in Promotion of Peace in Marawi City - LANGCO, MILHAYA DIANALAN (Jurnal Studi Pemerintahan, 2014)
This study determined the role of traditional Maranao leaders and local political leaders towards collaboration in promotion of peace in Marawi City. The study used the descriptive – explanatory research design. Descriptive statistics such as frequency counts and percentage distribution were used in the presentation and analysis of data. Furthermore, this study explored the association among variables. Pearson R tests were conducted to determine if there were associations between the traits and characteristics of Maranao traditional leaders and their role in promotion of peace; association between the administrative capabilities of local political leaders and their role in promotion of peace; both as independent variables, and association between roles of traditional and political leaders and their level of collaboration in promotion of peace, as the dependent variables. Percentage was used to quantitatively describe and analyze the responses given by the respondents while weighted mean was used to determine the average value of the responses in each item of the given questionnaire. Results of the findings revealed that the Sulutan was the highest traditional leader involved in conflict resolution while the Datu was the second most influential traditional leaders involved in the same. Furthermore, these traditional Maranao leaders is still seen by the respondents as honest and dependable, morally upright, tenacious and responsible, able to identify and clarify the needs and desires of groups, as well as that of the community as their priority. Moreover, the local political leaders in Marawi City including those of the Province of Lanao del Sur, are being seen to be important along with the Maranao traditional leaders in terms of conflict resolution and promotion of peace in the aforementioned areas.